2013
DOI: 10.1111/tan.12056
|View full text |Cite
|
Sign up to set email alerts
|

Association of 14‐bp insertion/deletion polymorphism of HLA‐G gene with unexplained recurrent spontaneous abortion: a meta‐analysis

Abstract: A meta-analysis was performed to assess the association of the human leukocyte antigen-G (HLA-G) 14 bp insertion (ins)/deletion (del) polymorphism with unexplained recurrent spontaneous abortions (URSA). The fixed or random effect pooled measure was selected based on the homogeneity test among studies that was evaluated with I². Odds ratio (OR) with 95% confidence interval (CI) was used to assess the strength of the association. In this meta-analysis, 14 studies with 1464 cases and 1247 controls corresponded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
5
36
1
6
Order By: Relevance
“…Our meta-analysis results were different from the outcomes of the previous metaanalysis of Wang et al 2013 [23]. After adding the study of ).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Our meta-analysis results were different from the outcomes of the previous metaanalysis of Wang et al 2013 [23]. After adding the study of ).…”
Section: Discussioncontrasting
confidence: 98%
“…But the results were controversial or inconclusive, partly because each study involved few cases and few controls and, therefore, there was not enough information to demonstrate such association. In a recent meta-analysis article of Wang et al(2013), it was suggested that the 14 bp ins HLA-G allele was associated with increased risk of RM [23]. The studies of Christiansen et al 2012 which were included in the metaanalysis of Wang et al(2013) were from the same study group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Другой путь формирования ВПС, ассоциированный с HLA-G, может быть связан с активацией вертикального пути пере-дачи вирусов от матерей к плоду. Показано, что ВИЧ и цитомегаловирус достоверно чаще пере-даются от инфицированных матерей к их детям при наличии у матерей аллелей или генотипов с HLA-G 3'UTR 14-bp ins [21]. Известно, что гер-петические вирусы индуцируют формирование ВПС.…”
Section: Discussionunclassified